Antioxidative Properties and HPLC Profile of Chloroform Fraction from Ethanolic Extract of the Peel of Citrus hystrix - Kah Weng Chua" (Science Faculty of Chiang Mai University, 2019)
Citrus fruits are known to possess high antioxidant activity due to active compounds present in it such as vitamins, carotenoids, flavonoids, and phytochemicals. The present study aimed to evaluate the antioxidant activity and total phenolic content of chloroform fraction from ethanol extract of peel of Citrus hystrix. The peel of C. hystrix was extracted with 77% ethanol and the crude extract was partitioned between hexane and formic acid (1:1). The formic acid layer was further fractionated with chloroform and n-butanol. The chloroform fraction showed the highest antioxidant activity; therefore it was subjected to further purification on column chromatography using hexane, ethyl acetate, and methanol in varying proportions. The eluates from the column were monitored using thin layer chromatography and aliquots with similar TLC profile were combined to give sub-fractions I, II, III, and IV. All the sub-fractions showed free radical scavenging activity. Qualitative HPLC analysis of all the sub-fractions showed presence of ascorbic acid, catechin, hesperetin, and apigenin; however, further purification and identification studies are needed to warrant their presence in the peel of C. hystrix.